Evidence mapping on how to perform an optimal surgical repair of large hiatal hernias - Nickel, Felix; Müller, Philip C.; Cizmic, Amila; Häberle, Frida; Müller, Markus K.; Billeter, Adrian; Linke, Georg R.; Mann, Oliver; Hackert, Thilo; Gutschow, Christian Alexander; Müller, Beat P. (Langenbeck's archives of surgery, 2023)
Symptomatic and large hiatal hernia (HH) is a common disorder requiring surgical management. However, there is a lack of systematic, evidence-based recommendations summarizing recent reviews on surgical treatment of symptomatic HH. Therefore, this systematic review aimed to create evidence mapping on the key technical issues of HH repair based on the highest available evidence.
Gesehen am 13.03.2024